Karakteristik Mutu Sensori Bakso Nabati Rumput Laut - Silvia Oktavia Nur Yudiastuti; Agung Wahyono; Titik Budiati; Maudiadwi Arsiwi (JOFE : Journal of Food Engineering, 2022)
Meatballs are a food favored by the community, with the number of buyers classified as frequent at +30% even though the calories are high, reaching 68 calories per piece with a fat content of 60%. The purpose of this study was to produce vegetable meatballs with lower fat but high fiber content. The vegetable meatballs in this study were produced using Eucheuma cottonii seaweed gel without meat and wheat flour as its raw materials. The vegetable meatballs can be intended for consumers with certain conditions. The research method used was experimental using a randomized block design (RAK). The treatment in this study was the concentration of E.cottonii seaweed gel in the product formulation which was 0.5%, 1%, 1.5%, 2%, and 2.5%. Each treatment was repeated three times. The observed response was consumers' acceptance using hedonic and hedonic quality tests and the fat content of meatballs. The results showed that vegetable meatballs with 1.5% gel content were the most preferred by panelists which contain 3.5% crude fiber and 14% fat.